Orthopedic Surgery Clerkship : A Quick Reference Guide for Senior Medical Students - Eltorai, Adam E. M.; Eberson, Craig P.; Daniels, Alan H. (Springer International Publishing : Imprint: Springer, 2017)
This quick-reference guide is the first book written specifically for the many third- and fourth-year medical students rotating on an orthopedic surgery service. Organized anatomically, it focuses on the diagnosis and management of the most common pathologic entities. Each chapter covers history, physical examination, imaging, and common diagnoses. For each diagnosis, the book sets out the typical presentation, options for non-operative and operative management, and expected outcomes. Chapters include key illustrations, quick-reference charts, tables, diagrams, and bulleted lists. Each chapter is co-authored by a senior resident or fellow and an established academic physician and is concise enough to be read in two or three hours. Students can read the text from cover to cover to gain a general foundation of knowledge that can be built upon when they begin their rotation, then use specific chapters to review a sub-specialty before starting a new rotation or seeing a patient with a sub-specialty attending. Practical and user-friendly, Orthopedic Surgery Clerkship is the ideal, on-the-spot resource for medical students and practitioners seeking fast facts on diagnosis and management. Its bullet-pointed outline format makes it a perfect quick-reference, and its content breadth covers the most commonly encountered orthopedic problems in practice.